PRECISE GEOCHRONOLOGY OF PHOSCORITES AND CARBONATITES: THE CRITICAL ROLE OF U-SERIES DISEQUILIBRIUM IN AGE INTERPRETATIONS - Amelin Y.; Zaitsev A.N. (My University, 2002)
We present the results of a comparative study of several geochronometer minerals (baddeleyite, zircon, apatite, phlogopite and tetraferriphlogopite) and isotopic systems (U-Pb, Th-Pb and Rb-Sr) from phoscorites (magnetite-forsterite-apatite-calcite rocks) and carbonatites of the Kovdor ultramafic-alkaline-carbonatite massif, Kola Peninsula, Russia. Uranium, thorium and their decay products are extremely fractionated by minerals that crystallise from carbonatite and phoscorite magma. We obtain high-precision ages from different chronometers, compare their accuracy, and evaluate the role of geochronological pitfalls of initial radioactive disequilibrium, differential migration of radiogenic isotopes, and inaccurate decay constants.Apatite yielded concordant U-Th-Pb ages between 376 and 380 Ma. The accuracy of the apatite 238U-206Pb ages is, however, compromised by uncertainty in the amount of radiogenic 206Pb produced from initial excess 230Th. The 235U-207Pb ages are relatively imprecise due to large common Pb correction and the uncertainty in the initial Pb isotopic composition. The Th-Pb system yields a more precise age of 376.4 ± 0.6 Ma.Zircon from two carbonatite samples is characterised by moderate to low U contents, high Th contents, and very high Th/U ratios up to 9000. The 206Pb*/238U systems in the zircon are strongly affected by the presence of excess 206Pb*, produced by decay of initial 230Th. The 208Pb*/232Th ages of zircon from both carbonatite samples are uniform and yield a weighted average of 377.52 ± 0.94 Ma.Baddeleyite U-Pb analyses are 3 to 6% normally discordant and have variable 207Pb*/206Pb* apparent ages. Eleven alteration-free baddeleyite fractions from three samples with no evidence for Pb loss yield uniform 206Pb*/238U ages with a weighted average of 378.54±0.23 Ma (378.64 Ma after correction for initial 230Th deficiency), which we consider the best estimate for age of the phoscorite-carbonatite body of the Kovdor massif. The 206Pb*/238U ages of baddeleyite fractions from five other samples spread between 378.5 and 373 Ma, indicating a variable lead loss up to 1.5%. The anomalously old 207Pb/235U and 207Pb/206Pb ages are consistent with the presence of excess radiogenic 207Pb* in the baddeleyite. We interpret this as a result of preferential partitioning of 231Pa to baddeleyite.Fifteen phlogopite and tetraferriphlogopite fractions from five carbonatite and phoscorite samples yielded precise Rb-Sr isochron age of 372.2 ± 1.5 Ma, which is 5 to 7 m.y. younger than our best estimate based on U-Th-Pb age values. This difference is unlikely to be a result of the disturbance or late closure of Rb-Sr system in phlogopite, but rather suggests that the accepted decay constant of 87Rb is too high.Comparative study of multiple geochronometer minerals from the Kovdor massif has revealed an exceptional complexity of isotopic systems. Reliable ages can be understood through systematic analysis of possible sources of distortion. No single geochronometer is sufficiently reliable in these rocks. Th-Pb and Rb-Sr can be a very useful supplement to U-Pb geochronometry, but the routine use of these geochronometers together will require more precise and accurate determination of decay constants for 232Th and 87Rb.